2022
DOI: 10.3390/biology11040569
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cultivation Substrate and Microbial Community on Improving Mushroom Productivity: A Review

Abstract: Lignocellulosic materials commonly serve as base substrates for mushroom production. Cellulose, hemicellulose, and lignin are the major components of lignocellulose materials. The composition of these components depends upon the plant species. Currently, composted and non-composted lignocellulosic materials are used as substrates in mushroom cultivation depending on the mushroom species. Different substrate compositions can directly affect the quality and quantity of mushroom production yields. Consequently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 158 publications
4
37
0
Order By: Relevance
“…The current study, showed that different mushroom isolates had different growth rates on both PDA and agricultural substrates. These findings were consistent with those of other research studies that reported that different mushroom species, isolates and growth substrates had a significant impact on the mycelial growth rate (Xing et al, 2018;Ly and Jitjak, 2020;Suwannarach et al, 2022). The high degree of mycelial growth was related to high hyphal extension and resulted in a very dense mycelial biomass (Carlile et al, 2001;Nashiruddin et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The current study, showed that different mushroom isolates had different growth rates on both PDA and agricultural substrates. These findings were consistent with those of other research studies that reported that different mushroom species, isolates and growth substrates had a significant impact on the mycelial growth rate (Xing et al, 2018;Ly and Jitjak, 2020;Suwannarach et al, 2022). The high degree of mycelial growth was related to high hyphal extension and resulted in a very dense mycelial biomass (Carlile et al, 2001;Nashiruddin et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, Hwang et al [123] reported that the EC value of the mycelium-colonized substrate (1.89 dS/m) was higher than that of the non-colonized substrate (1.12 dS/m). According to a number of previously published reports, an increase in the EC value in the substrate that had been colonized by mycelium could be explained by the fact that the substrate was degraded by an enzyme produced by the fungal mycelium, which also increased the amounts of inorganic compounds and minerals that were present, indicating a positive correlation with the EC value [98,124,125].…”
Section: Determination Of Chemical Propertiesmentioning
confidence: 99%
“…In addition to the physicochemical parameters, bacteria–fungi interactions also have a strong influence on mushroom production, ranging from antagonism to mutualism. Recent reports have attributed an important role to the compost and casing microbiome in the growth and fructification of cultivated mushrooms, mainly by influencing the quality and maturation of the compost, mycelium running, primordia induction and formation of fruit bodies [ 5 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%